Nursing home care and its influence onquality of life of the elderly:bibliographic review - Tizoc-Márquez, Arodi (Universidad de Sonora, 2019)
Introduction: With increasing age there is a decrease in physical, cognitive, and psychological abilities and this has given rise to a need for the elderly to receive the attention and care; thus the creation and spread of nursing home care facilities. Objective: To identify the influence of the stay in the nursing home on the quality of life of the elderly. Methodology: This is a bibliographic review, guided by recommendations of the PRISMA protocol, by means of a search in different recognized electronic databases, 959 primary papers were identified by region, and for the methodological evaluation the Checklist STROBE was used; after using the criteria 18 papers were obtained. It should be noted that nursing home care arose in response to the problems and needs of the elderly, however many elderly recipients of such care generally rate their experience as poor due to such things as various complications in living conditions, developing diseases as well as a lack of visitation by relatives. Results and conclusion: The quality of life of the institutionalized elderly is worsening as manifested in their physical, cognitive, and psycho-emotional functions. Additionally, there is the presence of chronic-degenerative diseases that represent a risk to the health and life expectancy of the elderly. Efforts must be made to promote public policies that support healthy aging.